2021
DOI: 10.3390/computation9030038
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of the Influence of Surface and Tooth Root Damage on the Stress and Strain State of a Planetary Gearbox: An Innovative Hybrid Numerical–Analytical Approach for Further Development of Structural Health Monitoring Models

Abstract: Wind turbine gearboxes are known to be among the weakest components in the system and the possibility to study and understand the behavior of geared transmissions when subject to several types of faults might be useful to plan maintenance and eventually reduce the costs by preventing further damage. The aim of this work is to develop a high-fidelity numerical model of a single-stage planetary gearbox selected as representative and to evaluate its behavior in the presence of surface fatigue and tooth-root bendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…the simulated eigenfrequencies were considered adequate and their estimation results in line with the experimental data. in conclusion, this work can be an effective starting point to setup a monitoring strategy of gearboxes and it can be a powerful tool to predict failures [17].…”
Section: Finite Element Methods (Fem)mentioning
confidence: 84%
“…the simulated eigenfrequencies were considered adequate and their estimation results in line with the experimental data. in conclusion, this work can be an effective starting point to setup a monitoring strategy of gearboxes and it can be a powerful tool to predict failures [17].…”
Section: Finite Element Methods (Fem)mentioning
confidence: 84%
“…Furthermore, mesh refinement is also required when the contacts and couplings of the variable rotating components are analyzed in order to obtain convergence with the simulated system. On the other hand, the model presented in this research paper solves, for each contact of the acting components, an additional equation through a relatively coarse grid [52]. This makes the computational effort relatively low, as the number of equations which need to be solved is reduced.…”
Section: Modeling Implementation and Numerical Simulationmentioning
confidence: 99%
“…This, in turn, can be projected onto both the surfaces in this solver stage and the contact pressures that are computed through this procedure, which are not sensitive to grid size. Therefore, additional details are given in [52].…”
Section: Modeling Implementation and Numerical Simulationmentioning
confidence: 99%
“…From this, they have found that gear pitting can cause varying degrees of reduction in the TVMS. Concli et al [5] used a hybrid numerical-analytical approach to study the impact of defects on stress. The results showed that the existence of pitting promoted an instantaneous increase in stress on the rim.…”
Section: Introductionmentioning
confidence: 99%